2005
DOI: 10.1038/sj.jcbfm.9600154
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Effects of Adenosine Receptor Agonists on Cerebral Blood Flow in Uninjured and Traumatically Injured Rat Brain using Continuous Arterial Spin-Labeled Magnetic Resonance Imaging

Abstract: Hypoperfusion after traumatic brain injury may exacerbate damage. Adenosine, a vasodilator, regulates cerebral blood flow (CBF). Treatment with adenosine receptor agonists has shown benefit in experimental CNS trauma; however, their effects on CBF after injury remain undefined. We used magnetic resonance imaging to assess CBF in uninjured rats both early and at 24 h after intrahippocampal administration of either the nonselective adenosine receptor agonist 2-chloroadenosine (2-CA, 12 nmol) or the A 2A -recepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 67 publications
(98 reference statements)
0
21
0
Order By: Relevance
“…On the other hand, one should not forget the neurodegererative and toxic effects that A 2A ARs exert at the central level [43][44][45][46][47][48][49]. In this context, A 2A AR hyperactivity may have important pathophysiological implications and might contribute to, induce or exacerbate neurodegenerative effects in several psychiatric diseases.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, one should not forget the neurodegererative and toxic effects that A 2A ARs exert at the central level [43][44][45][46][47][48][49]. In this context, A 2A AR hyperactivity may have important pathophysiological implications and might contribute to, induce or exacerbate neurodegenerative effects in several psychiatric diseases.…”
Section: Resultsmentioning
confidence: 99%
“…There are now at least four different variations on ASL including continuous ASL (CASL) (Detre and Alsop, 1999), pulsed ASL (PASL), cPASL (continuous PASL), and velocity selected ASL (VSASL) . ASL has been used to study rodent models of TBI (Forbes et al, 1997a,b;Hendrich et al, 1999;Kochanek et al, 2002Kochanek et al, , 2005Robertson et al, 2000), and has recently also been used in patient studies . Several promising potential applications for ASL in the study of TBI have been proposed, including characterization of regional brain function in severe TBI in which task-evoked responses are difficult to obtain, determination of the relationship between changes in regional CBF and cognitive deficits to identify potential targets for pharmacological therapy or other intervention, and use as a biomarker for pharmaceutical trials (Van Boven et al, 2009).…”
Section: Perfusion Imagingmentioning
confidence: 99%
“…Thus, there are short term adaptive neuronal responses that are operated through inhibitory A 1 receptors, namely in terms of the slow wave sleep [114] and cerebral metabolic activity [115,116]. There are also more long term adaptive changes, such as up-regulation of A 1 receptors [117,119] and possibly of A 2A receptors (reviewed in [57]) the former being a strong candidate to mediate the reduction of cerebral blood flow [116,[120][121][122], which is observed after these treatments. It should be made clear that at this stage there is a tentative parallel between the effects operated by these mood disorder treatments and the adenosine modulation system in the brain, but it still remain to be directly shown that the mood beneficial effects of these treatments is hampered by manipulation of adenosine receptors.…”
Section: Adenosine and Mood Disordersmentioning
confidence: 99%